PENGARUH KINERJA KEUANGAN BERBASIS PENCIPTAAN NILAI DAN DIVIDEND YIELD TERHADAP RETURN SAHAM PERUSAHAAN DI INDONESIA - Robbi Fernando Saputra (2021)
This study aims to determine the effect of Economic Value Added (EVA), Market Value Added (MVA), and dividend yield on stock returns of Kompas100 index companies on the Indonesia Stock Exchange (IDX). Stock returns are measured using a comparison of historical data on stock prices at the end of the observation period. EVA measurement is calculated using net operating profit after tax minus the company's cost of capital, MVA uses the difference between the company's market value and equity value, and the dividend yield is measured by the ratio between dividends per share and the company's stock price. Data collection methods used are observational techniques and literature study by observing stock prices and audited company financial statements through the sites www.idx.co.id, www.yahoo.finance.com and the sites of each company. The analytical method used is multiple linear regression analysis using STATA version 16. The population in this study is the Kompas100 index company on the IDX in 2017-2020. The research sample was determined using purposive sampling technique and 32 companies were obtained that matched the criteria. The results showed partially, EVA had a significant negative effect on stock returns, MVA has no effect on stock returns and dividend yields had a significant positive effect on stock returns.